Bullying in gifted and talented children: A systematic review - Febriana, Sri; Syafril, Syafrimen; Kuswanto, Cahniyo Wijaya (Atfaluna: Journal of Islamic Early Childhood Education, 2024)
The objective of this study was to carry out a systematic review of the research works that have analyzed bullying in gifted and talented children. The search was conducted in psychology and education databases (Scopus), considering works from the past 14 years (2009-2022). The research method used is the systematic literature review (SLR) method; the data is analyzed qualitatively, referring to the Milles and Huberman model, which includes data reduction, data presentation, and data validation. The search string in this study is